STRATEGI PENGEMBANGAN USAHA KERAJINAN TANGAN LIMBAH CANGKANG KERANG DI KOTA PAREPARE - Rahmanuddin, Andi; -, Nurhapsa; -, Arman (Jurnal Ilmiah Ecosystem, 2020)
Strategy for the Development of Shellfish Shell Waste Management Business in the city of Parepare under the guidance of Nurhapsa and Arman Reeng. The purpose of this study was to identify external and internal factors in the development of agribusiness-based shellfish waste business in the city of Parepare as well as to determine the strategy of developing the shellfish waste handicraft business development in the city of Parepare. The research was conducted in September 2017 in the City of Parepare. This type of research is descriptive research. Sampling using saturated or census sampling methods, the number of samples is 6 Waste Shell Craft Business. The data used in this study are primary data and secondary data. The analytical method used in this study is from the SWOT analysis. The results showed that internal factors (strengths and weaknesses) and external factors (opportunities and threats), the main strength factors were determined namely the presence of venture capital including light and the main weakness factor is the lack of marketing through social media, while the main opportunity factor is the presence of capital assistance from relevant agencies and the main threat factor is the high competition in the craft business in the same field. Based on the results of the SWOT analysis, the right alternative strategy to use is S-O, which is a strategy that uses power to take advantage of opportunities. The results of the establishment of an alternative S-O strategy are to use the strength of low venture capital for shellfish waste handicraft business to take advantage of opportunities for capital assistance from agencies related to the shellfish waste handicraft business.